PENGEMBANGAN PROGRAM KELAS LAPANG BUDIDAYA SILVOFISHERY UNTUK PEMBUDIDAYA IKAN DI KELURAHAN DEGAYU, KOTA PEKALONGAN - Ariadi, Heri; Fahrurrozi, Ashari; Ramadhani, Farchan Mushaf Al; Sulistiana, Ana; Linayati, Linayati (Universitas Mataram, 2024)
Silvofishery is an aquaculture concept that is integrated with the mangrove ecosystem. The concept of silvofishery cultivation is an environmental conservation model combined with the use of an integrated fish cultivation model. This silvofishery concept is very good to be developed in coastal waters. The hope is that in the future there will be activities to develop field class programs for silvofishery cultivation with various empowerment topics. The aim of this service is to make efforts to increase understanding and insight for fish farmers in Degayu Village regarding the silvofishery cultivation system which is carried out using the field class concept. The method used is community empowerment through practical education about silvofishery cultivation. Furthermore, in this practice, an impact analysis was also carried out by distributing participant response questionnaires. Next, the data from the questionnaire was analyzed descriptively. The results of the service showed that there was an increase in the ability and insight of fish farmers regarding silvofishery cultivation techniques by 40%, knowledge about feeding management by 80%, knowledge about water quality management by 40% and ability regarding feeding practices by 30%. This means that this silvofishery cultivation field class activity is very progressive in improving the quality of human resources for fish farmers. This silvofishery cultivation field class activity is also interesting enough to increase interest in aquaculture literacy for fish farmers. This cultivation field class model is highly recommended to always be carried out consistently as a form of knowledge transfer effort between practitioners (academics) and the program beneficiary audience. From this service activity it can be concluded that the service activity has had an impact on increasing understanding and insight for cultivators in the technical fields of silvofishery cultivation, feeding management, water quality management, and comprehensive technical feeding practices.